Employee–customer identification: Effect on Chinese online shopping experience, trust, and loyalty - Harash Sachdev; Matthew H. Sauber (Cogent Business & Management, 2023)
AbstractThis study investigates Chinese consumers’ interaction with retail employees and the effects on shopping experience, trust, and loyalty. Survey data help articulate brand comparison, digital interactions, and shopping experience as customer-identification change agents. A structural equation model highlights how consumers’ perception of employee identification enhances shopping experience, builds consumer trust, and improves loyalty. The study displays how customer trust mediates the effect of employee identification and retailer adaptability on customer loyalty while digital interaction mediates the effect of brand comparison on customer trust. The theoretical implications of these findings emphasise the importance of consumer-employee interaction in the identification process where the relationships between brand comparison, digital interaction, and shopping experience are highlighted in a retail setting. These results denote that (a) store loyalty is predominantly driven by consumer self-consistence and social conformance and (b) retailer online and offline interaction and coordination influence brand experiences and consumer retention.